Abulkhair Shibanid and the battle near the walls of Sygnak: to the question of Kazakh-Kalmyk relations in the XVth century - B. G. Ayagan (Nomadic Civilization: Historical Research, 2023)
The author of the article explores the issue of mentioning tribes known as “Oirats”, “Dzhungars” and “Kalmyks” in medieval sources. It is noted that in the literature this topic is reflected in oral traditions and written sources since the Middle Ages. To date, almost all major Kazakh legends and epics have been recorded, digitized and included in the register of written sources. Given that this topic requires fundamental research, the author deliberately confines himself to the chronological framework of the events of the XIV-XV centuries. During this period, the Oirats (Kalmyks) entered into versatile relations with the peoples and state formations of Mogolistan, the Khanate of Abulkhair and the Kazakh community. The author of the article gives a brief historiographical overview of the topic and expresses a number of hypotheses. At the same time, it is emphasized that information about the Kalmyks is available in the works of major medieval authors, for example, in the works of Muhammad Haidar Dulat, Mahmud bin Emir Wali, Masud Kukhistani, Fazlallah Ruzbikhan and others. Many of them were once introduced into scientific circulation in Kazakhstani historiography, but are less known in the historical science of Kalmykia. Based on the study of sources, the author believes that when considering this problem, the previously dominant political imperatives about the eternal enmity of the Kazakhs and the Dzungars, the Oirat-Kalmyks are already outdated and require a new understanding. Conservative approaches of the past prevented an objective study of the problem under consideration, which explains the relevance of the chosen topic.